P53 Exposure of infants to brominated flame retardants through breast-milk. Issue 6 (17th May 2019) - Kohn, E; Efreim, S; Lubetzky, R; Mandel, D; Marom, R; Betser, M; Keidar, R; Livne, A; Levy, A; Factor-Litvak, P; Soback, S; Britzi, M; et al.
Abstract : Introduction: Polybrominated Diphenyl Ethers (PBDEs) are non-biodegradable flame retardants, accumulated in biological systems and acting as endocrine disruptors. Breast feeding is a major route of exposure in infancy. Taken together with the critical development of this age and the potential adverse effects of PBDEs, it is important to monitor these contaminants in breastmilk. Objective: To evaluate the exposure of infants to PBDEs Methods: 343 families were recruited during 2013–2016 in Assaf Harofeh and Ichilov to create the AHI-EHF cohort. Maternal blood and urine, cord blood, breast milk and meconium were collected. Participants filled out questionnaires about socio-demographic status, medical history, exposures and life habits. Colostrum samples were collected from women at the maternity department. PBDEs in colostrum and Infant formulas levels were analyzed using GC-MS Results and discussion: Out of 183 serum samples, only 11(6%) detectable levels of PBDEs. PBDEs were found in all colostrum samples. The average concentration of total PBDEs in breastmilk was 714ng/L. PBDEs levels were also measured in three infant formulas. Unlike breastmilk, infant formulas had of only 3 congeners and levels were relatively low. The average concentration of total PBDEs in infant formulas was 153ng/L. PBDEs, were found to be negatively correlated to anno-penile index (API) which serve as a marker for endocrine disruption. Conclusions: PBDEs levels in breast milk are higher than levels in some European countries, but lower than in North America. PBDEs might have negative influence on AGD in boys. Maternal exposure to PBDEs and the significance of it should be further investigated. Disclosure(s): Nothing to disclose